2004
DOI: 10.1161/01.hyp.0000128243.06502.bc
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Differences Between Northern and Southern Chinese: Role of Dietary Factors

Abstract: Abstract-Blood pressure and prevalence of high blood pressure are greater for northern than southern Chinese. Reasons for these differences are unclear. Relationships of north-south blood pressure differences with multiple dietary factors were investigated in 839 Chinese participants, International Study on Macronutrients and Blood Pressure (INTERMAP), 561 northern, 278 southern, aged 40 to 59 years. Daily nutrient intakes were determined from four 24-hour dietary recalls and 2 timed 24-hour urine collections.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
127
2
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(142 citation statements)
references
References 24 publications
10
127
2
3
Order By: Relevance
“…Zhao et al 37 reported significant effects of dietary factors, including salt intake, on blood pressure differences between Chinese in the north (higher salt intake) and in the south (lower salt intake). As a limitation of the study, salt intake was not measured and thus cannot be adjusted; however, individual adjustment on a population factor can only have a limited effect within the same population.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al 37 reported significant effects of dietary factors, including salt intake, on blood pressure differences between Chinese in the north (higher salt intake) and in the south (lower salt intake). As a limitation of the study, salt intake was not measured and thus cannot be adjusted; however, individual adjustment on a population factor can only have a limited effect within the same population.…”
Section: Discussionmentioning
confidence: 99%
“…2 In Japan, the population-attributable fraction of hypertension for all-cause mortality is reported to be approximately 20%. 3 The findings of the INTERSALT and INTERMAP studies indicated a positive association between salt intake and blood pressure in multiethnic populations, [4][5][6][7] and evidence from randomized controlled trials has shown that a low sodium diet reduces blood pressure. [8][9][10] Although public health recommendations in most developed countries suggest reducing salt intake to 5-6 g day À1 , 11 the average salt intake in Japan is still higher than the recommendations (10.8 g day À1 , according to a national health and nutrition survey in 2006 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is striking that blood pressures are markedly higher in North than South China. 4,5 Etiology of high blood pressure…”
Section: Blood Pressures In East Asiamentioning
confidence: 99%
“…13 There is also evidence that 24 h urinary Na þ excretion and Na þ /K þ ratios are strongly associated with blood pressure in East Asians. 5 …”
Section: Blood Pressures In East Asiamentioning
confidence: 99%